Analysis of 220 ml cup supplier selection with AHP method and rating scale: case study PT. sabina tirta utama - Lumenta, Karine Nathania; Wahyuda, Wahyuda; Gunawan, Suwardi (Operations Excellence: Journal of Applied Industrial Engineering, 2023)
PT. Sabina Tirta Utama is a company that produces Bottled Drinking Water (AMDK) in 220 ml cup packaging. The company has problems related to 220 ml cup suppliers such as found in cup packaging with holes when the goods arrive, the quantity does not match the demand so the company needs suppliers who match the company's criteria and produce good quality packaging through supplier selection and assisted with the selection method. decision. The method used in supplier selection is AHP and rating scale. The AHP method is used to obtain global weight values which are then used to assist in ranking with the rating scale method. The purpose of this study was to determine the criteria and sub-criteria for a 220 ml cup and to identify priority suppliers. Supplier selection using 5 criteria and 11 sub-criteria. AHP weighting results on quality criteria is 0.197, price with a weight result of 0.296 delivery with a weight result of 0.401, communication system with a weight result of 0.035, and packaging capability of 0.07. The results of supplier ranking with a rating scale obtained the priority of the first supplier with a final assessment result of 3.551, namely supplier A with a high-performance category. Meanwhile, another alternative priority is supplier B with a final result of 2.641 in the performance category according to standards.